PENERAPAN MEDIA ASSEMBLER EDU BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Triana, Vivit; Wardani, Sri; Raharjo, Tri Joko; Subali, Bambang; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning that is still teacher-centered and not yet integrated with digital learning media causes students' low critical thinking abilities. The aim of the research is to determine the feasibility and effectiveness of using Augmented Reality-based EDU assembler media applied to class IV landscape material. The research method applied is the Borg n Gall development model with data collection techniques through observation, interviews, questionnaires, tests and documentation. The results of the trial carried out in the experimental class obtained a gain score of 0.7 with high criteria, while the control class obtained a gain score of 0.4 with low criteria, so it can be concluded that the use of EDU assembler media is effective in improving students' critical thinking skills.